El sistema bibliotecario de la Universidad de A Coruña - Fuentes Romero, Juan José (Revista General de Información y Documentación, 2003)
After an introductory analysis of the present state of affairs at universities and university libraries, the article studies the characteristics of the University of La Coruña giving a general outline of this university’s system before making, on the basis of data facilitated by REBUIN, a comparative analysis of this library with respect to other Spanish university libraries.